2008
DOI: 10.1021/bm701201w
|View full text |Cite
|
Sign up to set email alerts
|

Generating Elastic, Biodegradable Polyurethane/Poly(lactide-co-glycolide) Fibrous Sheets with Controlled Antibiotic Release via Two-Stream Electrospinning

Abstract: Damage control laparotomy is commonly applied to prevent compartment syndrome following trauma but is associated with new risks to the tissue, including infection. To address the need for biomaterials to improve abdominal laparotomy management, we fabricated an elastic, fibrous composite sheet with two distinct submicrometer fiber populations: biodegradable poly(ester urethane) urea (PEUU) and poly(lactide-co-glycolide) (PLGA), where the PLGA was loaded with the antibiotic tetracycline hydrochloride (PLGA-tet)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 39 publications
2
68
0
Order By: Relevance
“…The difference is also due to the factor of the different cell walls' structure of Gram-positive, which contain higher peptidoglycan than Gram-negative bacteria (Augustine et al 2014). Another study reported the use of TCH with different types of polymers for the treatment of infection in abdominal closure (Hong et al 2008). Electrospun TCH-loaded 10% (w/ w) nHA/PCL nanofibers could be efficient in use against bacterial infection at the bone interface.…”
Section: Antibacterial Activity and Tch Release Profilementioning
confidence: 99%
“…The difference is also due to the factor of the different cell walls' structure of Gram-positive, which contain higher peptidoglycan than Gram-negative bacteria (Augustine et al 2014). Another study reported the use of TCH with different types of polymers for the treatment of infection in abdominal closure (Hong et al 2008). Electrospun TCH-loaded 10% (w/ w) nHA/PCL nanofibers could be efficient in use against bacterial infection at the bone interface.…”
Section: Antibacterial Activity and Tch Release Profilementioning
confidence: 99%
“…Given their morphology and their mechanical performances, these scaffolds can be employed for TE of hard tissues, such as bone and cartilage. For such applications PLA e PLAGA copolymers with different compositions have been successfully foamed either as plain materials [117,125,129] or in combination with inorganic substances [87,130]. Moreover, scCO 2 foaming is a powerful technology for the production of scaffolds loaded with biomolecules such as growth factors [131][132][133][134][135] and DNA [134,135] that, once released, have been shown to maintain their activity.…”
Section: Gas Foamingmentioning
confidence: 99%
“…This opportunity has been extensively exploited to load fibres with biomolecules that were intended to be released upon contact with the biological environment. Among the several drugs employed, antibiotics [87][88][89], anti-inflammatory drugs [90][91][92] and anticancer drugs [93] have been mainly investigated.…”
Section: "Composite" Electrospun Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…34,94 New drug and gene delivery methods are emerging that will impart additional functionality, [129][130][131] potentially improving in vivo maturation rates and expanding the potential clinical application. Bioreactor systems that promote tissue growth via nutrient provision 132 and=or mechanical stimulation 133 will increasingly be utilized to foster nanofiber-based tissue development.…”
mentioning
confidence: 99%